Friends. Season 8 [videorecording (DVD)] - Aniston, Jennifer; Cox, Courteney, 1964-; Kudrow, Lisa; LeBlanc, Matt; Perry, Matthew, 1969-2023; Schwimmer, David, 1966-; Bright, Kevin, 1955-; Kauffman, Marta, 1956-; Crane, David, 1957- (Warner Bros., 2019)
Six young people, on their own and struggling to survive in the real world, find the companionship, comfort and support they get from each other to be the perfect antidote to the pressures of life. In Season 8, secrets abound. Who is the father of Rachel's baby? Why can't Phoebe stop thinking about her twin's fiancé? Why can't Joey keep his feelings to himself? And what's behind the locked door of Monica's closet?